Cell Exclusion in Couette Flow: Evaluation Through Flow Visualization and Mechanical Forces. Issue 3 (29th January 2013) - Leslie, Laura J.; Marshall, Lindsay J.; Devitt, Andrew; Hilton, Andrew; Tansley, Geoff D.
Abstract Cell exclusion is the phenomenon whereby the hematocrit and viscosity of blood decrease in areas of high stress. While this is well known in naturally occurring Poiseuille flow in the human body, it has never previously been shown in Couette flow, which occurs in implantable devices including blood pumps. The high‐shear stresses that occur in the gap between the boundaries in Couette flow are known to cause hemolysis in erythrocytes. We propose to mitigate this damage by initiating cell exclusion through the use of a spiral‐groove bearing (SGB) that will provide escape routes by which the cells may separate themselves from the plasma and the high stresses in the gap. The force between two bearings (one being the SGB) in Couette flow was measured. Stained erythrocytes, along with silver spheres of similar diameter to erythrocytes, were visualized across a transparent SGB at various gap heights. A reduction in the force across the bearing for human blood, compared with fluids of comparable viscosity, was found. This indicates a reduction in the viscosity of the fluid across the bearing due to a lowered hematocrit because of cell exclusion. The corresponding images clearly show both cells and spheres being excluded from the gap by entering the grooves. This is the first time the phenomenon of cell exclusion has been shown in Couette flow. It not only furthers our understanding of how blood responds to different flows but could also lead to improvements in the future design of medical devices.